Effect of transanal drainage tube on prevention of anastomotic leakage after anterior rectal cancer surgery taking indwelling time into consideration: a systematic review and meta-analysis - Xu, Xinzhen; Zhang, Xiang; Li, Xin; Yu, Ao; Zhang, Xiqiang; Dong, Shuohui; Liu, Zitian; Cheng, Zhiqiang; Wang, Kexin (Frontiers in Oncology, 2024)
Background Placement of an indwelling transanal drainage tube (TDT) to prevent anastomotic leakage (AL) after anterior rectal cancer surgery has become a routine choice for surgeons in the recent years. However, the specific indwelling time of the TDT has not been explored. We performed this meta-analysis and considered the indwelling time a critical factor in re-analyzing the effectiveness of TDT placement in prevention of AL after anterior rectal cancer surgery. Methods Randomized controlled trials (RCTs) and cohort studies which evaluated the effectiveness of TDT in prevention of AL after rectal cancer surgery and considered the indwelling time of TDT were identified using a predesigned search strategy in databases up to November 2022. This meta-analysis was performed to estimate the pooled AL rates (Overall and different AL grades) and reoperation rates at different TDT indwelling times and stoma statuses. Results Three RCTs and 15 cohort studies including 2381 cases with TDT and 2494 cases without TDT were considered eligible for inclusion. Our meta-analysis showed that the indwelling time of TDT for ≥5-days was associated with a significant reduction (TDT vs. Non-TDT) in overall AL (OR=0.46,95% CI 0.34-0.60, p<0.01), grade A+B AL (OR=0.64, 95% CI 0.42-0.97, p=0.03), grade C AL (OR=0.35, 95% CI 0.24-0.53, p<0.01), overall reoperation rate (OR=0.36, 95%CI 0.24-0.53, p<0.01) and that in patients without a prophylactic diverting stoma (DS) (OR=0.24, 95%CI 0.14-0.41, p<0.01). There were no statistically significant differences in any of the abovementioned indicators (p>0.05) when the indwelling time of TDT was less than 5 days. Conclusion Extending the postoperative indwelling time of TDT to 5 days may reduce the overall AL and the need for reoperation in patients without a prophylactic DS. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023407451, identifier CRD42023407451.